Factors influencing treatment adherence in paracoccidioidomycosis in Brazil - Wdson Luis Lima Kruschewsky; Ricardo Dal Col Batista; Hosana Ewald Oliveira; Aloísio Falqueto; Paulo Mendes Peçanha; Tânia Regina Grão Velloso; Sarah Gonçalves Tavares; Creuza Rachel Vicente (Wiley, 2023)
Abstract Introduction Paracoccidioidomycosis is a systemic mycosis endemic to Latin America, with frequent reports of poor treatment adherence resulting in worse clinical outcomes. The present study evaluated factors related to treatment adherence in patients with paracoccidioidomycosis. Methods This cross‐sectional study included data from medical records of patients with paracoccidioidomycosis treated between 2005 and 2018 in a reference hospital in southeastern Brazil. Clinical variables, demographic characteristics, and smoking and alcohol consumption were collected and analyzed. Results Of the 198 cases included, most were adults (median age = 51 years), males (93.4%), presented chronic paracoccidioidomycosis (83.8%), reported smoking (90.4%) and alcohol consumption (84.8%), and 56.6% adhered to treatment. Treatment adherence was associated with the discontinuation of alcohol consumption (odds ratios (OR) = 5.227; 95% confidence interval (CI) = 2.697-10.129) and smoking (OR = 3.365; 95% CI = 1.781-6.358) during therapy. Conclusions Patients' continued consumption of alcohol and tobacco was associated with non‐adherence to treatment, suggesting that a joint therapeutic approach that addresses alcohol and tobacco use alongside paracoccidioidomycosis treatment may hold promise for improving adherence and patients' quality of life.